High-speed chromatic confocal microscopy using multispectral sensors for sub-micrometer-precision microscopic surface profilometry. (December 2021) - Chen, Liang-Chia; Tan, Pei-Ju; Wu, Guo-Wei; Lin, Chih-Jer; Nguyen, Duc Trung
Abstract: A full-field chromatic confocal microscopy (CCM) using a multispectral sensor was developed for quasi-one-shot microscopic 3D surface measurement. An innovative optical configuration employs a digital micromirror device (DMD) and a multispectral sensor is used to realize CCM with full-field area scanning. In the optical design, an area-scan type chromatic dispersive objective is specially designed to achieve measuring specification. Based on a self-developed chromatic dispersive objective, the FOV for one shot measurement can be reached to 1.8×1.3 mm 2 which is immersive to microscopic profilometry. The spectral image captured by the multispectral sensor at each pinhole position has a unique spectrum pattern corresponding to its conjugate measured depth. A normalized cross-correlation (NCC) algorithm is developed to establish a spectrum-depth response curve with its corresponding spectrum pattern sets for accurate reconstruction of the tested 3D surface profile. With real test on standard targets, the measurement repeatability for a single surface depth is less than 0.6 μm.